2008
DOI: 10.1002/micr.20607
|View full text |Cite
|
Sign up to set email alerts
|

Quadriceps muscle reconstruction with free functioning latissimus dorsi muscle flap after oncological resection

Abstract: This method of reconstruction is a reliable technique not only to fill the defect resulting from oncological resection but also to provide better function. Microsurgical reconstruction of soft tissue sarcoma helps to expand the indications of limb salvage by allowing better local control and achieving adequate function and coverage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 35 publications
1
49
0
Order By: Relevance
“…Thereby, patients reached an average muscle manual test (MMT) score of 3 out of 5 and were capable of walking and stair climbing without support after an average follow-up of 69 months. 30 Muramatsu et al revealed even better results in 14 patients undergoing the same reconstructive procedure with an average MMT score of 4.8 after 79 months. 31 In a case series of Wechselberger et al 2 patients received free rectus femoris neurovascular muscle grafts for reconstruction of the opposite thigh extensors.…”
Section: Discussionmentioning
confidence: 94%
“…Thereby, patients reached an average muscle manual test (MMT) score of 3 out of 5 and were capable of walking and stair climbing without support after an average follow-up of 69 months. 30 Muramatsu et al revealed even better results in 14 patients undergoing the same reconstructive procedure with an average MMT score of 4.8 after 79 months. 31 In a case series of Wechselberger et al 2 patients received free rectus femoris neurovascular muscle grafts for reconstruction of the opposite thigh extensors.…”
Section: Discussionmentioning
confidence: 94%
“…Certain caveats exist regarding the use of free muscle transfers. First, given the prolonged duration of recovery of function, the use of this procedure should be carefully considered in patients with metastatic disease (23% of patients in one study 38 ). Although quality of life may be enhanced by functional reconstruction, other options, such as pedicled muscle transfer, should be considered.…”
Section: Free Functional Muscle Transfersmentioning
confidence: 99%
“…In cases in which the femoral periosteum has been removed, a proximally based portion of vascularised fascia lata can be inserted between bone and the transferred muscle to permit a gliding plane. 38 The muscle flap may be inserted with the proximal pole sutured to the tendon of rectus femoris proximally, or with bone anchors to the femur 37 (Figs 4 and 5).…”
Section: Free Functional Muscle Transfersmentioning
confidence: 99%
See 2 more Smart Citations